2020
DOI: 10.2147/dddt.s246574
|View full text |Cite
|
Sign up to set email alerts
|

<p>Combination Chemotherapy of Lung Cancer – Co-Delivery of Docetaxel Prodrug and Cisplatin Using Aptamer-Decorated Lipid–Polymer Hybrid Nanoparticles</p>

Abstract: Lung cancer is the leading cause of cancer mortality worldwide. Drug resistance is the major barrier for the treatment of non-small cell lung cancer (NSCLC). The aim of this research is to develop an aptamer-decorated hybrid nanoparticle for the co-delivery of docetaxel prodrug (DTXp) and cisplatin (DDP) and to treat lung cancer. Materials and Methods: Aptamer-conjugated lipid-polymer ligands and redox-sensitive docetaxel prodrug were synthesized. DTXp and DDP were loaded into the lipid-polymer hybrid nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Cell viability assays showed no significant cytotoxicity of blank NLC, which may be proof of the low toxicity of the materials used in the preparation (Wu et al., 2020 ). Chen et al reported a nanoparticle system and performed more efficient efficiency compared with free drugs on cancer cells (Chen et al., 2016 ).…”
Section: Discussionmentioning
confidence: 93%
“…Cell viability assays showed no significant cytotoxicity of blank NLC, which may be proof of the low toxicity of the materials used in the preparation (Wu et al., 2020 ). Chen et al reported a nanoparticle system and performed more efficient efficiency compared with free drugs on cancer cells (Chen et al., 2016 ).…”
Section: Discussionmentioning
confidence: 93%
“…Several commonly studied nanocarriers can be used to construct a co-delivery system that enables a synergistic effect between two or more medications [ 15 ]. The clinical treatment of cancer has utilized more than 20 nanotechnology-based therapeutic products [ 26 ]. With progression in the field of nanomaterials and nanotechnology, researchers have worked intensively to build multi-functional nanocarriers that can meticulously transport therapeutic agents to tumor sites [ 27 , 28 , 29 ].…”
Section: Nanocarriers Used In Co-delivery Systemsmentioning
confidence: 99%
“…Hence, there has been a surge in academic publications on co-delivery systems ascribed to the synergistic and undisruptive procedures these systems convey in treating diverse types of cancer [ 23 , 25 ]. To accomplish a guaranteed and efficient, targeted delivery of therapeutic drugs, an extensive interpretation of the interaction mechanism between the cancer cells and the DDS is essential [ 14 , 26 ]. The scope of this review was to address recent progress in the field of nanotechnology for combination therapy used in co-delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the one-step method only requires a mixing of lipid and polymer, which lead both materials to selfassemble. In a recent study, a selective targeting of LPHNPs was explored by conjugating the carrier with aptamer (APT) to deliver cisplatin (CDDP) and DCX for combination therapy of NSCLC [125]. Prior to drug loading into the NPs, DCX is conjugated with glyceryl monostearate (GM) to produce a redox-sensitive DCX prodrug (DCXp).…”
Section: Lipid-polymer Hybrid Nanoparticles (Lphnps)mentioning
confidence: 99%